A Maternal-Administered Multimodal Neonatal Bundle in Hospitalized Very Preterm Infants: A Pilot Study. (April 2021) - Letzkus, Lisa; Alonzo, Corrie; Connaughton, Elizabeth; Kelly, Nancy; Zanelli, Santina
Abstract : Background: Premature infants are at an increased risk for developing cerebral palsy (CP). Evidence-based strategies designed to promote healthy brain development and facilitate adaptation after brain injury in infants still admitted to the neonatal intensive care unit (NICU) represent a novel approach that may lead to improved long-term outcomes. Purpose: To investigate the feasibility of a maternal-administered early intervention bundle in very preterm infants prior to NICU discharge. Methods: A pilot trial evaluating a maternal-administered NICU-based bundle of interventions in preterm infants (⩽32 weeks' gestational age and/or ⩽1500 g birth weight). The impact of the bundle on short-term developmental outcomes of infants, as well as maternal stress, anxiety, and depression, is evaluated. Results: The intervention bundle was implemented in 11 mother–infant dyads (including 1 set of twins) for a median of 8 weeks and was overall well received. Vocal soothing, scent exchange, and comforting touch were feasible, performed at or above the predetermined goal of 71% of the time (5/7 days), while kangaroo care and infant massage were not. Maternal stress, anxiety, and depression were decreased during the study time. Implications to Practice: A neonatal multimodal intervention bundle provided by mothers is feasible. Implications to Research: Additional randomized controlled studies are needed to determine whether this type of bundled interventions can (1) improve the neurodevelopmental outcomes of participating infants and (2) improve long-term parental outcomes, including decreased burden of anxiety and depression, as well as improved attachment and optimal patterns of social interaction.